2019
DOI: 10.3390/nu11020244
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and Characterization of Quercetin-loaded Oil in Water Nanoemulsion and Evaluation of Hypocholesterolemic Activity in Rats

Abstract: Due to poor water solubility and high susceptibility to chemical degradation, the applications of quercetin have been limited. This study investigated the effects of pH on the formation of quercetin-loaded nanoemulsion (NQ) and compared the hypocholesterolemic activity between quercetin and NQ to utilize the quercetin as functional food ingredient. NQ particle size exhibited a range of 207–289 nm with polydispersity index range (<0.47). The encapsulation efficiency increased stepwise from 56 to 92% as the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 62 publications
4
27
0
4
Order By: Relevance
“…Encapsulation efficiency of curcumin in NE found in this study (90.36 ± 0.002%) was in accordance with the results of Mohanty and Sahoo (2010) with entrapment efficiency of (90 ± 2.55%), and 90.56 ± 0.47% reported by Sari et al (2015). The encapsulation efficiency for quercetin was reported to vary from 56% to 92% with the increase in pH from 4 to 9 (Son et al, 2019). In this study, encapsulation efficiency for quercetin was found to be 92.58 ± 0.001%, while due to hydrophilic nature of gallic acid, low encapsulation efficiency 86.85 ± 0.3 was found in this study.…”
Section: Encapsulation Efficiencysupporting
confidence: 90%
“…Encapsulation efficiency of curcumin in NE found in this study (90.36 ± 0.002%) was in accordance with the results of Mohanty and Sahoo (2010) with entrapment efficiency of (90 ± 2.55%), and 90.56 ± 0.47% reported by Sari et al (2015). The encapsulation efficiency for quercetin was reported to vary from 56% to 92% with the increase in pH from 4 to 9 (Son et al, 2019). In this study, encapsulation efficiency for quercetin was found to be 92.58 ± 0.001%, while due to hydrophilic nature of gallic acid, low encapsulation efficiency 86.85 ± 0.3 was found in this study.…”
Section: Encapsulation Efficiencysupporting
confidence: 90%
“…Promote conversion of cholesterol to bile acids and cholesterol efflux by increasing hepatic CYP7A1 activity and hepatic LXRα, ABCG1, and LDLR protein expressions [116] ApoE −/− mice Elevate cholesterol accepting ability of HDL and increase ABCA1/G1 expression levels of proteins related to RCT [117] Sprague-Dawley rats Influence gene and protein expression of SREBP1c and HMGR to lower lipid [118] Sprague-Dawley rats Upregulate hepatic gene expression CYP7A1, LXRα, ABCA1, and ABCG1 to promote cholesterol efflux [119] Zucker rats Lower the level of HDL cholesterol and increase phosphorus level by increasing the ratio of ASAT/ALAT activity induced by leptin [56] ApoE −/− mice Regulate expressions of ABCA1, LXRα, and PCSK9 [26] ApoE −/− mice Downregulate PCSK9 and CD36 protein expression and upregulate PPAR c, LXRα, and ABCA1 protein expression levels in both the aortic and liver tissues [65] Alter the gut microbiota ApoE −/− mice Regulate primary bile acid biosynthesis [95] C57BL/6J mice Improve composition and functionality of gut microbiome and production of short chain fatty acids [120] Wistar rats Stimulate bacterial enzymatic activity and increase enzymatic activity of the intestinal microbiota [121] Ldlr −/− mice Reduce MDA, cholesterol, and LPC 18 : 1 and increase IL-6 and coprostanol levels [98] Humans Anti-inflammation…”
Section: Elimination Of Etiology Reduction Of Complications and Effmentioning
confidence: 99%
“…In the pH range of 6.5-9, NQ was stored for 3 m at 21 and 37 °C with good stability. [35] Compared with quercetin, NQ was more effective in reducing serum liver cholesterol levels and increasing the release of bile acids into feces in rats fed a high-cholesterol diet. Chen et al prepared quercetin emulsions to improve the biological availability of quercetin, a hydrophobic nutrient.…”
Section: Son Et Al Prepared Quercetin Nanoemulsion (Nq) Andmentioning
confidence: 97%